What are the factors of tax evasion? New findings in the EVS study - Tereza Ryšavá; Hana Zídková (Review of Economic Perspectives, 2021)
This paper is analyzing tax morale in three selected European countries through the evaluation of the results of the European Values Study. The main aim is to identify the factors that influence taxpayers' decisions on the issue of whether they justify cheating on tax or not. The dependence and effect of selected factors were determined by analyzing data from the latest European Values Study (2019). The analysis revealed that not only demographic factors (gender, age), but also other socio-economic and institutional factors (religion, willingness to defend the home country, being a proud citizen, trust in government and respect for authorities) have a significant impact on taxpayers' justification of cheating on taxes. This research is specifically focused on the Czech Republic, Poland and Spain.
Keywords: H26; H31; K34; 330; European Values Study; chi-square test; tax avoidance; tax compliance; tax morale